Mummy math : an adventure in geometry - Neuschwander, Cindy; Langdo, Bryan (New York : Henry Holt, 2005)
Matt and Bibi accompany their scientist parents to Egypt to search for the mummy of an ancient pharoah, and after becoming lost in the pyramid, must use their geometry skills to decipher the clues encoded in the hieroglyphics to locate the burial chamber and find their way out again.
4.7
3-6
Keywords: Pyramid (Geometry) -- Juvenile literature; Pyramids -- Juvenile literature; Geometry, Solid -- Juvenile literature; Pyramid (Geometry); Pyramids; Geometry, Solid; Pyramids; Solid geometry